2000
DOI: 10.1063/1.373723
|View full text |Cite
|
Sign up to set email alerts
|

In-plane lattice thermal conductivity of a quantum-dot superlattice

Abstract: We have theoretically investigated the in-plane lattice thermal conductivity of a quantum-dot superlattice. The calculations were carried out for a structure that consists of multiple layers of Si with randomly distributed Ge quantum dots separated by wetting layers and spacers. Our model takes into account scattering of acoustic phonons on spherical quantum dots, and corresponding modification of the phonon dispersion relation. The finite acoustic mismatch between Si and Ge is also taken into account. The obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 7 publications
0
57
0
2
Order By: Relevance
“…Both electrons and phonons contribute to the thermal contribution (κ = κ e + κ ph ) and lower values of any of them will yield higher values of ZT . Kithun et al reported high values of the figure of merit in a quantum-dot superlattice due to strong phonon scattering [4]. Chang and Nikolić have demonstrated that nanopore arrays in graphene nanoribbons can block phonons while retaining edge electron currents, yielding ZT ≈ 5 [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both electrons and phonons contribute to the thermal contribution (κ = κ e + κ ph ) and lower values of any of them will yield higher values of ZT . Kithun et al reported high values of the figure of merit in a quantum-dot superlattice due to strong phonon scattering [4]. Chang and Nikolić have demonstrated that nanopore arrays in graphene nanoribbons can block phonons while retaining edge electron currents, yielding ZT ≈ 5 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Since the advent of nanotechnology, many discoveries have demonstrated that nanometersized objects exhibit physical properties not shared by bulk materials [2]. In particular, theoretical predictions [3][4][5] and experiments [6][7][8][9] pointed out that thermoelectric properties at the nanoscale are strongly enhanced. Efficient thermoelectric bulk materials display values of ZT lower than unity.…”
Section: Introductionmentioning
confidence: 99%
“…1 Also, for a given mass fraction of particles, a larger quantity of smaller particles may yield lower k c . 19 The scattering of phonons during these events is not spatially uniform but instead occurs preferentially in certain directions. The exact spatial distribution depends on many variables, including phonon wavelength, particle size, and particle arrangement.…”
Section: Zt = S Te 2 E T Te K C ͑1͒mentioning
confidence: 99%
“…There are three possible reasons for the increase in the Seebeck coefficient: (1) The layered SiB=B=GeB nanostructure may enhance interface scattering and improve the Seebeck coefficient similarly to the superlattice interface. 36) (2) The diameter of the nanodots formed in the films is sufficiently small to enhance σ-density, which has a strong binding effect on carriers. This results in asymmetric migration of carriers and an increase in the Seebeck coefficient.…”
Section: )mentioning
confidence: 99%